1977
DOI: 10.1007/bf01565918
|View full text |Cite
|
Sign up to set email alerts
|

Complications of surgery for gastroesophageal reflux

Abstract: In the course of approximately 350 operations for gastroesophageal reflux and 1,500 evaluations of patients previously operated on or being assessed for therapy, a number of complications and undesirable side effects of antireflux surgery have been encountered. This report describes unfavorable outcomes including postoperative dysphagia, “gas‐bloat syndrome,” postoperative gastric dilatation, unplanned vagotomy, failure to relieve symptoms, persistence or recurrence of reflux or hiatal hernia, perforation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
7

Year Published

1981
1981
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 16 publications
0
10
0
7
Order By: Relevance
“…Skinner reported increased numbers of tertiary contractions in the distal esophagus in patients with dysphagia occurring after a Nissen procedure [16]. In our study no significant motility disturbances, not even during meals, were found to explain dysphagia.…”
Section: Discussionmentioning
confidence: 49%
“…Skinner reported increased numbers of tertiary contractions in the distal esophagus in patients with dysphagia occurring after a Nissen procedure [16]. In our study no significant motility disturbances, not even during meals, were found to explain dysphagia.…”
Section: Discussionmentioning
confidence: 49%
“…The presence of a Maloney dilator within the esophageal lumen gives con fidence to the surgeon that he is not pulling the gastric fundus too tight. The 60-french dilator corresponds to the diameter of the gullet sufficient to accommodate a large bolus of food [18], and its clinical use is supported by previous experience [3]. The observation that stenting the esophagus with a standard bougie yields satisfactory pressure values after Nissen fundoplication suggests that intraoperative manometry is an unnecessary and timeconsuming procedure, since it can be effectively replaced by simple mechanical calibration.…”
Section: Discussionmentioning
confidence: 77%
“…This operation is, however, associated with a number of postoperative complications, in particular with a relatively high incidence rate of dysphagia; incidence rates ranging from 5% to 43% have been reported following conventional fundoplication [8,9,10], requiring reoperation for dysphagia in up to 25% of patients [5]. A major cause of dysphagia is the creation of a 360°wrap [11,12,13,14,15,16,17,18,19]. This has led to the use of procedures entailing the creation of a partial wrap.…”
Section: Discussionmentioning
confidence: 95%